ASAS OPORTUNITAS SEBAGAI DASAR PENYAMPINGAN PERKARA PIDANA OLEH JAKSA AGUNG RI : STUDI KASUS PENYAMPINGAN PERKARA ABRAHAM SAMAD - Hikmah Oktaviani, - (2019)
The Prosecutor's Office is the only institution authorized to prosecute. Prosecution is carried out by the Public Prosecutor against a person suspected of committing a criminal offense, to be subsequently brought to the realm of the Court in accordance with the principle of legality adopted by Indonesia. However the Prosecutor is also authorized by the Act not to prosecute in accordance with the conditions that have been determined based on the principle of opportunity. The policy for not demanding is divided into 2 (two), namely the termination of prosecution and adjudication of cases. Termination of cases or often referred to as seponering and deponering is one of the rights that is only owned by the Attorney General of the Republic of Indonesia which aims at the public interest and is the application of opportunistic principles in accordance with Article 35 letter C of Law Number 16 of 2004 concerning Republican Prosecutors Indonesia. In this study, the author will discuss the application of opportunistic principles in the criminal cases, ranging from the legislation governing them, implementation and list of cases that have been ruled out by the Attorney General from time to time. In addition, it will also be discussed regarding the legal consequences for suspects whose cases have been ruled out. The determination of the waiver issued by the Attorney General is final and the legal status of the suspect will disappear by itself. Then the provision cannot be sued by pretrial because it is not included in the object. The possibility of revocation of these provisions by the Attorney General is considered very small, because when making decisions it has considered various aspects such as juridical, philosophical and sociological aspects. Revocation will also conflict with one of the principles of law enforcement, namely legal certainty. Henceforth, it is expected that the Prosecutor's Office can open information, especially regarding the case adjournment, to make it easier for the public to know it and become a reference for research material. The author uses normative research methods or literature by examining theories, concepts, legal principles and legislation related to this research.